Microporous asymmetric organic / inorganic composite membrane

By developing a porous ion permeable asymmetric composite membrane with asymmetric pore structure and more hydrophilic characteristics, the high ion resistance problems caused by the hydrophobicity and low wettability of the separator materials in traditional AEL systems are solved, and a more efficient and lower-cost AEL system performance is achieved.

CN119768563APending Publication Date: 2025-04-04UOP LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380060916.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-31
Filing Date
2023-08-28
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In existing alkaline water electrolysis (AEL) systems, the microstructure and chemical composition of the separator have a great impact on performance, but traditional materials such as polysulfone and polyphenylene sulfide have hydrophobicity and low wettability, resulting in high ionic resistance, limiting system efficiency and cost reduction.

Method used

A porous ion permeable asymmetric composite membrane was developed, using an asymmetric porous structure and a more hydrophilic polymer coating, combining porous substrates and inorganic particles, improving the mechanical strength, thermal stability and wettability of the membrane, thereby reducing ion resistance.

Benefits of technology

The new diaphragm exhibits high mechanical strength, low ion resistance and good thermal stability under high pH environments, significantly improving the efficiency of the AEL system and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768563A_ABST
    Figure CN119768563A_ABST
Patent Text Reader

Abstract

A porous ion-permeable membrane with an asymmetric pore structure is described, wherein the top of the membrane (the side opposite the porous substrate) has smaller pores than the pores in the rest of the polymer coating (i.e., closer to the porous substrate). The porous ion-permeable asymmetric composite membrane comprises a polymer, inorganic particles, and a porous substrate, the porous substrate being stable at a pH of 8 or higher.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Priority declaration

[0002] This application claims priority to U.S. Provisional Patent Application Serial No. 63 / 374,030 filed on August 31, 2022, the entire contents of which are incorporated herein by reference. Background Art

[0003] Hydrogen plays an important role on the road to an environmentally friendly, low-carbon energy structure as an energy carrier for grid balancing or power-to-gas and power-to-liquid processes. Water electrolysis produces high-quality hydrogen by electrochemically decomposing water into hydrogen and oxygen; the reaction is given by Equation 1 below. The water electrolysis process is an endothermic process, and electricity is the energy source. When the process is operated by renewable energy such as wind, solar or geothermal energy, water electrolysis has a zero carbon footprint. The main commercially available water electrolysis technologies include alkaline water electrolysis (AEL) and proton exchange membrane (PEM) water electrolysis (PEMWE, such as Figure 1 shown).

[0004] like Figure 1 As shown, in the PEMWE system 100, the anode 105 and the cathode 110 are separated by a solid PEM electrolyte 115, such as the one shown in the trademark A fluorinated copolymer based on sulfonated tetrafluoroethylene sold by the Chemours company. The anode and cathode catalysts typically contain IrO2 and Pt, respectively. At the positively charged anode 105, pure water 120 is oxidized to produce oxygen 125, electrons (e - ) and protons; the reaction is given by Equation 2. Protons are transported from the anode 105 to the cathode 110 through the proton-conducting PEM 115. At the negatively charged cathode 110, a reduction reaction occurs in which electrons from the cathode 110 are given to protons to form hydrogen 130; the reaction is given by Equation 3. The PEM 115 not only conducts protons from the anode 105 to the cathode 110, but also separates the H2 gas 130 and O2 gas 125 produced in the water electrolysis reaction. PEM water electrolysis is one of the advantageous methods for converting renewable energy into high-purity hydrogen, with the advantages of compact system design at high pressure difference, high current density, high efficiency, fast response, small footprint, low temperature (20°C-90°C) operation, and high-purity oxygen byproduct. However, one of the main challenges of PEMWE is the high capital cost of the cell stack, including expensive acid-resistant stack hardware (such as Pt-coated Ti bipolar plates), expensive precious metal catalysts required for electrodes, and expensive PEMs.

[0005] Water electrolysis reaction: 2H2O→2H2+O2(1)

[0006] Anodic oxidation reaction of PEMWE: 2 H2O → O2 + 4 H + + 4 e - (2)

[0007] Cathodic reduction reaction of PEMWE: 2 H + + 2 e - → H2 (3)

[0008] In the long term, AEL is likely to remain the dominant electrolysis technology, especially for large-scale hydrogen production (gigawatt scale), because it uses lower-cost materials such as steel and nickel rather than expensive platinum and iridium.

[0009] In recent years, the development of AEL technology has been intensified in order to further optimize the components of AEL systems, improve efficiency and reduce costs. In addition to new electrocatalysts, the focus has been on the development and optimization of other cell components, especially separators. The separator is a porous barrier placed between the electrodes to prevent the product gases from mixing directly within the electrolytic cell. Asbestos was originally used as a membrane in water electrolysis cells until this material was banned due to health concerns. Polysulfone (PSU) and polyphenylene sulfide (PPS) have been selected as promising new materials to replace asbestos. However, these polymers are slightly hydrophobic and have low wettability with electrolyte solutions (25 wt%-30 wt% KOH), resulting in high ionic resistance. Therefore, hydrophilic materials (such as inorganic particles or other polymers) are added to improve the overall wettability. The composite material exhibits improved chemical and mechanical stability and electrolyte wettability. A typical example is Zirfon, which consists of a polysulfone matrix and zirconium dioxide (ZrO2). TM Porous composite separators. Currently, Zirfon manufactured by Agfa TM The diaphragm is the most well-known diaphragm for AEL.

[0010] For this type of composite separators, the overall performance strongly depends on the detailed microstructure and chemical composition. Zrifon TM The membrane has a symmetrical structure, which increases the ion transport resistance.

[0011] Therefore, it is desirable to develop new separators with optimized pore structures and with more hydrophilic materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 is a diagram of one embodiment of a PEMWE battery.

[0013] Figure 2 is a cross-sectional HRSEM image of the membrane prepared in Example 4. DETAILED DESCRIPTION

[0014] A novel porous ion-permeable membrane with an asymmetric pore structure and a more hydrophilic polymer coating has been developed for alkaline water electrolysis applications. The membrane has high pH stability at pH 8 or higher, a bubble point of 1 bar or higher, a porosity of 40% or higher, and an ionic resistance of 350 mΩ.cm 2 The porous ion permeable asymmetric composite membrane can transfer hydroxide ions (OH) to the electrolyte in the presence of an alkaline aqueous solution in an alkaline water electrolyzer. - ) is transported from the cathode to the anode, and the generated hydrogen and oxygen are prevented from mixing at the cathode and the anode, respectively. The porous ion permeable asymmetric composite membrane comprises a porous substrate and a porous asymmetric polymer coating. The polymer coating has an asymmetric pore distribution, wherein the pores with a first size are adjacent to the porous substrate and the pores smaller than the first size are adjacent to the second side (that is, the pores at the top (the side opposite to the porous substrate) are smaller than the pores in the rest of the polymer coating). The polymer coating comprises a polymer and inorganic particles. The polymer, inorganic particles and porous substrate are stable at a pH of 8 or higher.

[0015] The polymer coating has an asymmetric structure. The top of the membrane (the side opposite the porous substrate) has smaller pores than the pores in the rest of the polymer coating (ie, closer to the porous substrate).

[0016] The polymer coating should have high mechanical strength, including high pressure resistance up to 100 bar, good thermal stability up to at least 150°C, high pH stability at pH 8 or higher, and be hydrophilic. Suitable polymers include, but are not limited to, polyethersulfone (PES), polysulfone (PSU), polyvinylidene fluoride (PVDF), or a combination thereof. In some embodiments, PES is used because it has higher mechanical and thermal properties and higher chemical resistance than PSU. In addition, PES has a more polar portion, making it slightly more hydrophilic, which is useful for AEL's diaphragm material. PES also exhibits high stability in a high concentration KOH solution at 80°C.

[0017] Inorganic particles are present in the polymer coating. Suitable inorganic particles include, but are not limited to, zirconium oxide, iron oxide, nickel oxide, cobalt oxide, copper oxide, manganese oxide, molybdenum oxide, titanium oxide, antimony oxide, or a combination thereof. In some embodiments, the inorganic particles include zirconium oxide, antimony oxide, or a mixture thereof. The inorganic particles may account for 10% to 90% by weight, or 20% to 90% by weight, or 30% to 90% by weight, or 40% to 90% by weight, or 50% to 90% by weight, or 60% to 90% by weight of the polymer coating. Since the membrane is porous, the particle size is not particularly limited; however, the size should be selected so that the particles are not easily precipitated from the solution.

[0018] The membrane is prepared on a porous substrate to improve mechanical strength. The porous substrate may include polyphenylene sulfide, poly(ether ether ketone), polytetrafluoroethylene, polyethylene, polypropylene, copolymers of tetrafluoroethylene and ethylene, copolymers of tetrafluoroethylene and propylene, copolymers of ethylene and propylene, polychlorotrifluoroethylene, or combinations thereof. In some embodiments, the porous substrate includes polyphenylene sulfide or poly(ether ether ketone).

[0019] In some embodiments, the porous substrate has a 0.5 ft 3 / ft 2 In some embodiments, the porous substrate has an open area of ​​20% to 90%, or 30% to 90%, or 40% to 90%, or 50% to 90%, or 60% to 90%.

[0020] In some embodiments, the polymer in the polymer coating is different from the polymer of the porous substrate.

[0021] The asymmetric structure provides low ionic resistance. The pore size and pore distribution of the membrane can be controlled by varying the fabrication parameters, such as the concentration of the polymer, the amount of inorganic particles, the nonsolvent, and the temperature of the coagulation bath.

[0022] In one embodiment, the composite membrane comprises a PES matrix, ZrO2 nanopowder and a PPS porous substrate. This combination has the advantages of low cost, high stability under AEL operating conditions and high ion conductivity. Therefore, the membrane can improve AEL efficiency and reduce costs.

[0023] Another aspect of the present invention is a method for preparing a porous ion-permeable asymmetric composite membrane. In one embodiment, the method includes: mixing a polymer, an inorganic particle and a solvent, and the polymer and the inorganic particle are stable at a pH of 8 or higher to form a membrane casting material; casting the membrane casting material on a porous substrate to form a polymer coating on the porous substrate, the polymer coating having an asymmetric pore distribution, wherein pores having a first size are adjacent to the porous substrate and pores having a size smaller than the first size are adjacent to the second side, the porous substrate is stable at a pH of 8 or higher, and the polymer coating on the porous substrate forms a wet film; and annealing the wet film to form a stable porous ion-permeable asymmetric composite membrane. In some embodiments, the wet porous ion-permeable asymmetric composite membrane is dried at 50°C to 150°C, or 50°C to 120°C, or 60°C to 90°C.

[0024] A homogeneous casting material is formed by mixing the polymer, inorganic particles and a solvent. Suitable solvents include, but are not limited to, N-methyl-2-pyrrolidone (NMP), dimethylacetamide (DMAc), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), 1,3-dioxolane, acetone, methanol, ethanol, tetrahydrofuran (THF), toluene, n-octane, n-decane, lactic acid, citric acid, isopropanol or mixtures thereof.

[0025] Suitable casting processes include, but are not limited to, phase inversion processes via doctor blade casting or Meyer rod casting, slot die coating, dip coating, meniscus coating, gravure coating, or combinations thereof.

[0026] In some embodiments, the solvent may be removed from the polymer coating and the porous substrate prior to annealing the wet film. In addition to removing the solvent, this may also cure the wet film. Suitable solvent removal processes include, but are not limited to, water washing and / or solvent exchange.

[0027] The wet film is annealed to stabilize the pore structure of the film. Suitable annealing processes include, but are not limited to, annealing the wet film in hot water at a temperature in the range of 50°C to 90°C or 65°C to 90°C.

[0028] The annealed wet film may be dried. Suitable drying processes include, but are not limited to, direct air drying at 50°C to 100°C or 60°C to 90°C, or other suitable drying processes.

[0029] Another aspect of the present invention is the use of a porous ion-permeable asymmetric composite membrane for an AEL. In one embodiment, the AEL cell comprises: a porous ion-permeable asymmetric composite membrane as described above; an anode comprising an anode catalyst on a first surface of the porous ion-permeable asymmetric composite membrane; and a cathode comprising a cathode catalyst on a second surface of the porous ion-permeable asymmetric composite membrane. An alkaline solution (such as a KOH solution) is introduced into both the cathode and the anode. Water decomposes at the cathode to form H2 and release hydroxide anions (OH - ), the hydroxide anions pass through the microporous membrane and combine at the anode to form O2.

[0030] Anode catalyst and cathode catalyst are used for oxygen evolution reaction and hydrogen evolution reaction respectively. Anode catalyst and cathode catalyst should have low cost and good electrocatalytic activity and stability. Suitable cathode catalyst can be selected from but not limited to Ni, Ni-C, Ni-based alloys (such as Ni-Mo, Ni-Al, Ni-Cr, Ni-Sn, Ni-Co, Ni-W and Ni-Al-Mo), metal carbides (such as Mo2C), metal phosphides (such as CoP), metal dichalcogenides (such as MoSe2), high specific surface area Ni catalysts (such as Nickel-Zn ​​and Ni-Al) obtained by dealloying Ni-based alloys, and mixtures thereof. Suitable anode catalysts can be selected from but not limited to Ni-Fe, Ni-Mo, Ni-Co-Fe, spinel Cu x Co 3x O3, Ni-Fe layered binary hydroxide nanoplates on carbon nanotubes, immobilized metal catalysts on conductive supports, and mixtures thereof.

[0031] In some embodiments, the anode comprising an anode catalyst on the first surface of the porous ion-permeable asymmetric composite membrane is formed by coating the anode catalyst ink on the first surface of the porous ion-permeable asymmetric composite membrane via meniscus coating, doctor blade coating, spray coating, painting or other known conventional ink coating techniques, and then drying the coated porous ion-permeable asymmetric composite membrane.

[0032] In some embodiments, the cathode comprising a cathode catalyst on the second surface of the porous ion-permeable asymmetric composite membrane is formed by coating the cathode catalyst ink on the second surface of the porous ion-permeable asymmetric composite membrane via meniscus coating, doctor blade coating, spray coating, painting or other known conventional ink coating techniques, and then drying the coated porous ion-permeable asymmetric composite membrane.

[0033] In some embodiments, the anode catalyst ink comprises an anode catalyst, OH as a binder, - In some embodiments, the cathode catalyst ink comprises a cathode catalyst, an OH group as a binder, - Exchange ionomer and solvent. OH - The exchange of ionomer binders generates OH between the reactive sites in the membrane and the electrode. - transport channels, thus greatly improving the utilization of electrocatalyst particles while reducing internal resistance. - The ion exchange polymer binder may have a chemical structure similar to the anion exchange polymers described above, such that the binder will achieve low interfacial resistance and similar swelling upon contact with water to avoid catalyst delamination, but maintain OH -Conductivity and high oxygen and hydrogen permeability. The solvent may be selected from, but not limited to, water, alcohol or mixtures thereof.

[0034] In some embodiments, the anode and cathode are not coated on the surface of the porous ion-permeable asymmetric composite membrane.

[0035] Example

[0036] Example 1 :

[0037] In a glass jar, 57g of zirconium oxide (ZrO2) nanopowder (E101, LuxferMEL Technologies) was mixed with 45.6g of N-methyl-2-pyrrolidone (NMP, Millipore Sigma) using an overhead mixer for 30 minutes. After the ZrO2 powder was completely wetted in NMP, the first batch of 3g of polyethersulfone (PES, BASF Corporation) was added and stirred for 1 hour. The glass jar was placed in an ultrasonic bath and sonicated for 10 minutes. Then a second batch of 4g of PES was added, stirred for 1 hour and sonicated for 10 minutes. Then a third batch of 3g of PES was added, stirred for 1 hour and sonicated for 10 minutes. Finally, 3g of polyvinylpyrrolidone (PVP, Fisher Scientific) was added and stirred for 1 hour. The weight ratio of PES / PVP / ZrO2 was 10 / 3 / 57. The glass jar was then placed on a roller mixer and mixed for 16 hours to form a white viscous slurry for film casting.

[0038] Polyphenylene sulfide (PPS, PVF Mesh & Screen Technology) mesh is glued to a glass plate. The white slurry is poured on the PPS net and cast using a casting knife with a scraper gap of 10 mils to form a wet film. The wet film is immediately soaked in isopropyl alcohol (IPA) for 30 minutes. Then, the film is soaked in deionized (DI) water for 30 minutes, then soaked in deionized water for 30 minutes for the second time, and soaked in deionized water for 2 hours for the third time. The film is annealed in an 80°C water bath for 30 minutes and dried in an 85°C oven for 1 hour.

[0039] Example 2 :

[0040] In a glass jar, 90g ZrO2 nano powder (E101, Luxfer MELTechnologies) was mixed with 56.7g NMP for 30 minutes using an overhead mixer. After the ZrO2 powder was completely wetted in NMP, the first batch of 3g PES was added and stirred for 1 hour. The glass jar was placed in an ultrasonic bath and ultrasonicated for 10 minutes. Then the second batch of 4g PES was added, stirred for 1 hour and ultrasonicated for 10 minutes. Then the third batch of 3g PES was added, stirred for 1 hour and ultrasonicated for 10 minutes. Finally, 3g PVP was added and stirred for 1 hour. The weight ratio of PES / PVP / ZrO2 was 10 / 3 / 90. The glass jar was then placed on a roller mixer and mixed for 16 hours to form a white viscous slurry for film casting.

[0041] The PPS mesh was glued to a glass plate. The white slurry was poured onto the PPS mesh and cast using a casting knife with a doctor blade gap of 10 mils to form a wet film. The wet film was immediately soaked in IPA for 30 minutes. Then, the film was soaked in deionized water for 30 minutes, followed by a second soak in deionized water for 30 minutes, and a third soak in deionized water for 2 hours. The film was annealed in an 80°C water bath for 30 minutes and dried in an 85°C oven for 1 hour.

[0042] Example 3 :

[0043] In a glass jar, 90g ZrO2 nano powder (E101, Luxfer MELTechnologies) was mixed with 56.7g NMP for 30 minutes using an overhead mixer. After the ZrO2 powder was completely wetted in NMP, the first batch of 3g PES was added and stirred for 1 hour. The glass jar was placed in an ultrasonic bath and ultrasonicated for 10 minutes. Then the second batch of 4g PES was added, stirred for 1 hour and ultrasonicated for 10 minutes. Then the third batch of 3g PES was added, stirred for 1 hour and ultrasonicated for 10 minutes. Finally, 4g PVP was added and stirred for 1 hour. The weight ratio of PES / PVP / ZrO2 was 10 / 4 / 90. The glass jar was then placed on a roller mixer and mixed for 16 hours to form a white viscous slurry for film casting.

[0044] The PPS mesh was glued to a glass plate. The white slurry was poured onto the PPS mesh and cast using a casting knife with a doctor blade gap of 10 mils to form a wet film. The wet film was immediately soaked in IPA for 30 minutes. Then, the film was soaked in deionized water for 30 minutes, followed by a second soak in deionized water for 30 minutes, and a third soak in deionized water for 2 hours. The film was annealed in an 80°C water bath for 30 minutes and dried in an 85°C oven for 1 hour.

[0045] Example 4 :

[0046] In a glass jar, 90g ZrO2 nano powder (E101, Luxfer MELTechnologies) was mixed with 56.7g NMP for 30 minutes using an overhead mixer. After the ZrO2 powder was completely wetted in NMP, the first batch of 3g PES was added and stirred for 1 hour. The glass jar was placed in an ultrasonic bath and ultrasonicated for 10 minutes. Then the second batch of 4g PES was added, stirred for 1 hour and ultrasonicated for 10 minutes. Then the third batch of 3g PES was added, stirred for 1 hour and ultrasonicated for 10 minutes. Finally, 4g PVP was added and stirred for 1 hour. The weight ratio of PES / PVP / ZrO2 was 10 / 4 / 90. The glass jar was then placed on a roller mixer and mixed for 16 hours to form a white viscous slurry for film casting.

[0047] The PPS mesh was glued to a glass plate. The white slurry was poured onto the PPS mesh and cast using a casting knife with a doctor blade gap of 10 mils to form a wet film. The wet film was immediately soaked in deionized water for 5 minutes, followed by a second soak in deionized water for 1 hour, a third soak in deionized water for 1 hour, and a fourth soak in deionized water for 1 hour. The film was then soaked in IPA for 1 hour, followed by a second soak in IPA for 1 hour. The film was annealed in an 80°C water bath for 30 minutes and dried in an 85°C oven for 1 hour.

[0048] The membrane was tested for water permeability using a liquid permeation test unit. The membrane was sealed in a Sterlitech test container, the feed side was filled with deionized water and connected to high pressure nitrogen to regulate the feed pressure. The permeated water was collected in a glass jar, which was placed on a balance to measure the weight of water that permeated through the membrane over a period of time.

[0049] The water permeability of the membranes of Examples 1 to 4 is listed in Table 1. When the ZrO2 concentration and / or PVP concentration in the membrane casting slurry is increased, the water permeability increases. When the wet membrane is immersed in water for phase inversion, the prepared membrane is thicker, has a more open structure, and exhibits much higher water permeability.

[0050] Table 1: Water permeability of membranes

[0051]

[0052] Example 5 :

[0053] In a glass jar, 70g ZrO2 nano powder (E101, Luxfer MELTechnologies) was mixed with 56.7g NMP for 30 minutes using an overhead mixer. After the ZrO2 powder was completely wetted in NMP, the first batch of 3g PES was added and stirred for 1 hour. The glass jar was placed in an ultrasonic bath and ultrasonicated for 10 minutes. Then the second batch of 4g PES was added, stirred for 1 hour and ultrasonicated for 10 minutes. Then the third batch of 3g PES was added, stirred for 1 hour and ultrasonicated for 10 minutes. Finally, 4g PVP was added and stirred for 1 hour. The weight ratio of PES / PVP / ZrO2 was 10 / 4 / 70. The glass jar was then placed on a roller mixer and mixed for 16 hours to form a white viscous slurry for film casting.

[0054] The PPS mesh was glued to a glass plate. The white slurry was poured onto the PPS mesh and cast using a casting knife with a doctor blade gap of 10 mils to form a wet film. The wet film was immediately soaked in deionized water for 5 minutes, followed by a second soak in deionized water for 1 hour, a third soak in deionized water for 1 hour, and a fourth soak in deionized water for 1 hour. The film was then soaked in IPA for 1 hour, followed by a second soak in IPA for 1 hour. The film was annealed in an 80°C water bath for 30 minutes and dried in an 85°C oven for 1 hour.

[0055] The ionic resistance of the membrane was measured using a flow battery test cell (Fuel Cell Store) with 30% KOH as the electrolyte solution. The membrane was sealed between two gaskets and the test area was 5 cm 2 Both sides of the membrane were filled with KOH solution and circulated at 30 mL / min. The resistance of the electrolyte without the membrane was first measured. Then, the total resistance of the membrane and the electrolyte was measured. The ionic resistance of the membrane is equal to the total resistance minus the resistance of the electrolyte.

[0056] The ionic resistance of the membranes of Examples 1 to 3 and 5 is listed in Table 2. When the ZrO2 concentration and / or PVP concentration in the membrane casting slurry is increased, the ionic resistance decreases. When the wet membrane is immersed in water for phase inversion, the prepared membrane is thicker, has a more open structure, and exhibits much lower ionic resistance.

[0057] Table 2: Ionic resistance of membranes

[0058]

[0059] Specific implementation plan

[0060] While the following is described in conjunction with specific embodiments, it should be understood that this description is intended to illustrate and not to limit the scope of the foregoing description and the appended claims.

[0061] The first embodiment of the present invention is a porous ion-permeable asymmetric composite membrane for electrolysis, the porous ion-permeable asymmetric composite membrane comprising: a porous substrate; and a porous asymmetric polymer coating, the porous asymmetric polymer coating having a first side and a second side, the first side being on the porous substrate, the polymer coating comprising a polymer and inorganic particles, the polymer coating having an asymmetric pore distribution, wherein pores having a first size are adjacent to the porous substrate and pores having a size smaller than the first size are adjacent to the second side; and wherein the porous substrate, the polymer and the inorganic particles are stable at a pH of 8 or higher. One embodiment of the present invention is one, any one or all of the first embodiment of this paragraph to the previous embodiment of this paragraph, wherein the polymer comprises polyethersulfone, polysulfone, polyvinylidene fluoride or a combination thereof. One embodiment of the present invention is one, any one or all of the first embodiment of this paragraph to the previous embodiment of this paragraph, wherein the inorganic particles comprise zirconium oxide, iron oxide, nickel oxide, cobalt oxide, copper oxide, manganese oxide, molybdenum oxide, titanium oxide, antimony oxide or a combination thereof. One embodiment of the present invention is one, any or all of the first embodiment of this paragraph to the previous embodiment of this paragraph, wherein the inorganic particles include zirconium oxide, antimony oxide or a combination thereof. One embodiment of the present invention is one, any or all of the first embodiment of this paragraph to the previous embodiment of this paragraph, wherein the inorganic particles account for 10% to 90% by weight of the polymer coating. One embodiment of the present invention is one, any or all of the first embodiment of this paragraph to the previous embodiment of this paragraph, wherein the porous substrate has 0.5 ft 3 / ft 2 / min or more air permeability and 20% or more open area. One embodiment of the present invention is one, any one or all of the first embodiment of this paragraph to the previous embodiments of this paragraph, wherein the porous substrate comprises polyphenylene sulfide, poly(ether ether ketone), polytetrafluoroethylene, polyethylene, polypropylene, a copolymer of tetrafluoroethylene and ethylene, a copolymer of tetrafluoroethylene and propylene, a copolymer of ethylene and propylene, polychlorotrifluoroethylene or a combination thereof. One embodiment of the present invention is one, any one or all of the first embodiment of this paragraph to the previous embodiments of this paragraph, wherein the porous substrate comprises polyphenylene sulfide or poly(ether ether ketone). One embodiment of the present invention is one, any one or all of the first embodiment of this paragraph to the previous embodiments of this paragraph, wherein the polymer is different from the porous substrate.

[0062] The second embodiment of the present invention is a method for preparing a porous ion-permeable asymmetric composite membrane, the method comprising: mixing a polymer, an inorganic particle and a solvent, the polymer and the inorganic particle being stable at a pH of 8 or higher to form a membrane casting material; casting the membrane casting material on a porous substrate to form a polymer coating on the porous substrate, the polymer coating having an asymmetric pore distribution, wherein pores having a first size are adjacent to the porous substrate and pores having a size smaller than the first size are adjacent to the second side, the porous substrate being stable at a pH of 8 or higher, the polymer coating on the porous substrate forming a wet film; and annealing the wet film to form the stable porous ion-permeable asymmetric composite membrane. An embodiment of the present invention is one, any one or all of the second embodiment of this paragraph to the previous embodiment of this paragraph, the method further comprising drying the porous ion-permeable asymmetric composite membrane after annealing the wet membrane. One embodiment of the present invention is one, any one or all of the second embodiment of this paragraph to the previous embodiment of this paragraph, wherein the porous ion-permeable asymmetric composite membrane is dried at a temperature in the range of 50°C to 100°C. One embodiment of the present invention is one, any one or all of the second embodiment of this paragraph to the previous embodiment of this paragraph, wherein the method further comprises removing the solvent from the polymer coating and the porous substrate before annealing the wet membrane. One embodiment of the present invention is one, any one or all of the second embodiment of this paragraph to the previous embodiment of this paragraph, wherein the wet membrane is annealed in hot water at a temperature in the range of 50°C to 90°C. One embodiment of the present invention is one, any or all of the second embodiment of this paragraph to the previous embodiment of this paragraph, wherein the solvent includes N-methyl-2-pyrrolidone (NMP), dimethylacetamide (DMAc), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), 1,3-dioxolane, acetone, methanol, ethanol, tetrahydrofuran (THF), toluene, n-octane, n-decane, lactic acid, citric acid, isopropanol or a mixture thereof. One embodiment of the present invention is one, any or all of the second embodiment of this paragraph to the previous embodiment of this paragraph, wherein the polymer includes polyethersulfone, polysulfone, polyvinylidene fluoride or a combination thereof. One embodiment of the present invention is one, any or all of the second embodiment of this paragraph to the previous embodiment of this paragraph, wherein the inorganic particles include zirconium oxide, iron oxide, nickel oxide, cobalt oxide, copper oxide, manganese oxide, molybdenum oxide, titanium oxide, antimony oxide or a combination thereof.One embodiment of the present invention is one, any or all of the second embodiment of this paragraph to the previous embodiment of this paragraph, wherein the porous substrate comprises polyphenylene sulfide, poly(ether ether ketone), polytetrafluoroethylene, polyethylene, polypropylene, copolymers of tetrafluoroethylene and ethylene, copolymers of tetrafluoroethylene and propylene, copolymers of ethylene and propylene, polychlorotrifluoroethylene or a combination thereof. One embodiment of the present invention is one, any or all of the second embodiment of this paragraph to the previous embodiment of this paragraph, wherein the inorganic particles account for 10% to 90% by weight of the polymer coating. One embodiment of the present invention is one, any or all of the second embodiment of this paragraph to the previous embodiment of this paragraph, wherein the polymer is different from the porous substrate.

[0063] Although there is no further detailed description, it is believed that those skilled in the art can utilize the present invention to the greatest extent by using the foregoing description and can easily determine the essential characteristics of the present invention without departing from the spirit and scope of the present invention to make various changes and modifications of the present invention and adapt it to various usages and conditions. Therefore, the aforementioned preferred specific embodiments should be understood as merely illustrative and not to limit the rest of the present disclosure in any way, and are intended to cover various modifications and equivalent arrangements included within the scope of the appended claims.

[0064] In the foregoing, all temperatures are set forth in degrees Celsius and all parts and percentages are by weight unless otherwise indicated.

Claims

1. A porous ion-permeable asymmetric composite membrane for electrolysis, the porous ion-permeable asymmetric composite membrane comprising: a porous substrate; and a porous asymmetric polymer coating having a first side and a second side, the first side being on the porous substrate, the polymer coating comprising a polymer and inorganic particles, the polymer coating having an asymmetric pore distribution wherein pores having a first size are adjacent to the porous substrate and pores having a size smaller than the first size are adjacent to the second side; wherein the porous substrate, the polymer and the inorganic particles are stable at a pH of 8 or higher.

2. The membrane of claim 1, wherein the polymer comprises polyethersulfone, polysulfone, polyvinylidene fluoride, or a combination thereof.

3. The film of any one of claims 1 to 2, wherein the inorganic particles comprise zirconium oxide, iron oxide, nickel oxide, cobalt oxide, copper oxide, manganese oxide, molybdenum oxide, titanium oxide, antimony oxide, or a combination thereof.

4. The film of any one of claims 1 to 2, wherein the inorganic particles comprise 10 wt% to 90 wt% of the polymer coating.

5. The membrane according to any one of claims 1 to 2, wherein the porous substrate has a 0.5 ft 3 / ft 2 / min or more air permeability and 20% or more open area.

6. The membrane of any one of claims 1 to 2, wherein the porous substrate comprises polyphenylene sulfide, poly(etheretherketone), polytetrafluoroethylene, polyethylene, polypropylene, copolymers of tetrafluoroethylene and ethylene, copolymers of tetrafluoroethylene and propylene, copolymers of ethylene and propylene, polychlorotrifluoroethylene, or combinations thereof.

7. The membrane of any one of claims 1 to 2, wherein the polymer is different from the porous substrate.

8. A method for preparing a porous ion-permeable asymmetric composite membrane, the method comprising: mixing a polymer, inorganic particles, and a solvent, wherein the polymer and the inorganic particles are stable at a pH of 8 or higher to form a film casting material; casting the membrane casting on a porous substrate to form a polymer coating on the porous substrate, the polymer coating having an asymmetric pore distribution wherein pores having a first size are adjacent to the porous substrate and pores having a size smaller than the first size are adjacent to a second side, the porous substrate being stable at a pH of 8 or greater, the polymer coating on the porous substrate forming a wet film; as well as The wet membrane is annealed to form the stable porous ion-permeable asymmetric composite membrane.

9. The method according to claim 8, further comprising: drying the porous ion-permeable asymmetric composite membrane after annealing the wet membrane; or removing the solvent from the polymer coating and the porous substrate prior to annealing the wet film; Or both.

10. The method according to any one of claims 8 to 9, wherein the solvent comprises N-methyl-2-pyrrolidone (NMP), dimethylacetamide (DMAc), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), 1,3-dioxolane, acetone, methanol, ethanol, tetrahydrofuran (THF), toluene, n-octane, n-decane, lactic acid, citric acid, isopropanol or a mixture thereof.